Structural Equation Modeling of Drivers’ Situation Awareness Considering Road and Driver Factors - Yang, Yanqun; Chen, Meifeng; Wu, Changxu; Easa, Said M.; Zheng, Xinyi (Frontiers in Psychology, 2020)
Driver’s situation awareness (SA) is one of the key elements that affect driving decision-making and driving behavior. SA is influenced by many factors, and previous studies have focused only on individual factors. This study presents a comprehensive study to explore the path relationships and influence mechanism between SA and all influential factors, including road characteristics, driver characteristics and states, distracting elements, and cognitive ability. A structural equation model that relates SA to its influential factors is developed. A total of 324 valid questionnaires were collected to analyze and identify the relationships between the factors. The results show that the preceding influential factors have significant effects on SA, which was consistent with previous research. Based on path coefficients, positive effects were : cognitive abilities (0.500), driver state (0.360), age (0.277), driving experience (0.198), and gender (0.156). Negative effects were: distracting elements (-0.253) and road characteristics (-0.213). The results of this comprehensive study provide a valuable reference for the development of driver training programs and driving regulations.